2017
DOI: 10.1002/acr.22937
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐Reported Outcomes Measurement Information System Tools for Collecting Patient‐Reported Outcomes in Children With Juvenile Arthritis

Abstract: Objective To evaluate the precision and construct validity of pediatric Patient Reported Outcomes Measurement Information System® (PROMIS®) instruments in a population of juvenile idiopathic arthritis (JIA) patients and parent proxies. Methods A convenience sample of JIA patients and parents of JIA patients completed PROMIS instruments for eight domains: anger, anxiety, depressive symptoms, fatigue, mobility, pain interference, peer relationships, and upper extremity function. Short form and computerized ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 30 publications
5
55
3
Order By: Relevance
“…11,12 The domain and sum scores as reported in the present study in Dutch children were higher than previous reported data in UK, Romania and Lithuania. Differences between child and parent proxy scores were also reported in other paediatric PROMs, and the recommendation is to measure both perspectives.…”
Section: Comparison With Other Studiescontrasting
confidence: 83%
“…11,12 The domain and sum scores as reported in the present study in Dutch children were higher than previous reported data in UK, Romania and Lithuania. Differences between child and parent proxy scores were also reported in other paediatric PROMs, and the recommendation is to measure both perspectives.…”
Section: Comparison With Other Studiescontrasting
confidence: 83%
“…In recent years, the focus of health care has been drifting toward the inclusion of health-related quality of life (HRQoL) outcomes for patients in research and daily clinical practice by administering patient-reported outcome measures (PROMs) (1)(2)(3)(4)(5)(6). Previous studies have shown that rheumatology could benefit greatly from the use of patient-reported outcomes, as patients experience a wide array of problems (7) for which there is a disconnect between patient-reported outcomes and outcomes reported | 1781 by parents or clinicians (8). In clinical practice, there are often multiple PROMs available to measure the same construct/domain that differ in content, length, and scoring methods.…”
Section: Introductionmentioning
confidence: 99%
“…If the computer network was down or the participant preferred paper, static eight‐item short forms were used. A previous study in children with juvenile arthritis found equivalence between the PROMIS Pediatric CAT and short forms . Each question's recall period was “the past 7 days,” and the questions had five response categories.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study in children with juvenile arthritis found equivalence between the PROMIS Pediatric CAT and short forms. 22 Each question's recall period was "the past 7 days," and the questions had five response categories. The PROMIS Pediatric scores were on a T-score metric with mean of 50 (standard deviation of 10) in the original calibration sample.…”
Section: Methodsmentioning
confidence: 99%